Pilot test of a virtual reality-based psychoeducation program for family caregivers caring for post-stroke survivors - Sukadiono, Sukadiono; Mundakir, Mundakir; Hakim, Lukman; Choliq, Idham; Fitriyani, Vika Ramadhana; Syarifurrahman, Islam; Nasrullah, Dede (Kontakt, 2025)
According to recent research, many family caregivers lack the necessary knowledge and skills to provide effective care for individuals who have survived a stroke. Interventions such as psychoeducational training have demonstrated the potential to enhance caregiver competence and patient outcomes. Utilizing virtual reality to deliver educational content to family caregivers represents a novel approach to addressing the challenges encountered by caregivers of post-stroke survivors. In a quasi-experimental study employing a one-group, pre-test and post-test design, we recruited a cohort of 30 family caregivers responsible for providing care to stroke survivors within their homes. The study sample was drawn from a hospital in Surabaya, Indonesia. Participating family caregivers of stroke survivors completed a four-week psychoeducational program, following which data on effectiveness and feasibility were collected. The findings revealed a statistically significant reduction in the DASS-42 score after the program (t = 31.22, p < 0.001), indicating that the psychoeducational program was perceived as beneficial for family caregivers of stroke patients. Subsequently, the next phase will involve the implementation of the psychoeducational program with a broader group of family caregivers of stroke survivors.
Keywords: psychoedukace; Pilot Projects; rodina; Stroke; Family; Caregivers; lidé; Virtual Reality; Humans; cévní mozková příhoda; osoby pečující o pacienty; duševní zdraví; Mental Health; pilotní projekty; virtuální realita